RESPONSE OF DOSEMETERS IN FIELDS GENERATED BY LASER-ACCELERATED PROTONS - Olšovcová, V; Versaci, R; Ambrožová, I; Zelenka, Z; Kaufman, J; Margarone, D; Kim, I J; Jeong, T M (Radiation protection dosimetry, 2016)
In laser-driven acceleration, ultra-short and intense laser pulses are focussed on targets to generate beams of ionising radiation. One of the most important issues to be addressed is personal monitoring. While traditional dosemeters were designed primarily for measurements in continuous fields, dosemeters for laser laboratories must be capable of working in pulsed fields of pulse length below 1 ps, in a single-shot regime up to the repetition rate of 1 kHz. Responses of conventional dosemeters (films, polyallyldiglycol carbonate, electronic personal dosemeter) to proton bunches of up to 30 MeV energy produced by South Korean PW laser system at the Advanced Photonics Research Institute, Gwangju Institute of Science and Technology were studied, both by means of Monte Carlo simulations and experimentally.
Keywords: uhličitany; filmová dozimetrie; glykoly; Film Dosimetry; Radiation Monitoring; protony; Plastics; Korejská republika; Radiation, Ionizing; Radiation Dosimeters; počítačová simulace; Republic of Korea; Reproducibility of Results; dozimetry; lidé; Calibration; Monte Carlo Method; Carbonates; plastické hmoty; Glycols; ionizující záření; Computer Simulation; kalibrace; reprodukovatelnost výsledků; Lasers; monitorování radiace; metoda Monte Carlo; lasery; Protons; Radiation Dosage; dávka záření; Humans